Development of cryopreservation techniques for freezing oocytes and pre-embryos - Erasmus, Evelyn Lynette (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.(Med. Physiology)) -- University of Stellenbosch, 1989.